Analisis Evaluasi Sensorik pada Formulasi Produk Sosis dengan Substitusi Bahan Pengganti Kulit Ayam: Literature Review - Afifah, Lyna Nur; Adi, Annis Catur (Universitas Airlangga, 2024)
Background: Chicken sausage is one of the most widely produced meat products with low production costs, using simple technology and minimal equipment. There is a lot of research has developed chicken sausage products by substituting chicken skin with other ingredients such as food fiber and by-products from other chicken cuts. Objectives: analyze the quality of chicken sausage from the sensory side of products that experienced substituting raw chicken skin with other ingredients based on research on existing formulations. Methods: this study used the literature review and comes from several journal database sources, such as Google Scholar, PubMed, Science Direct with articles criteria that discuss about development of chicken sausage food products made from chicken skin. Results: Based on the results of a literature search, the results of 4 studies that examined sensory analysis of chicken sausage products were obtained after the chicken skin raw material was substituted with other ingredients. Conslusion: The difference in sensory analysis results in the four studies was influenced by the ingredients used to substitute chicken skin. In addition, the differences in the selection and assessment of the panelists were influenced by each individual's perception of the product given the treatment.